Extra hepatic bile ducta carcinoma - Fernandes, Rubens Henrique (2022)
The authors review the clinics presentation, diagnosis and treatment of the hilar cholangiocarcinoma. The essentials exams for staging and choice ofthe best therapeutics are discussed. The advances in knowledge about this phatology provide new curative and palliative tecnics that are presented in this review.